Facebook democracy : the architecture of disclosure and the threat to public life - Marichal, José. (Politics & international relations., 2016)
Drawing on a number of disciplines and an ethnographic analysis of 250 Facebook political groups, Marichal explores how Facebook's emphasis on social connection impacts key dimensions of political participation: e.g. mobilization, deliberation, and attitude formation.